Analisis Faktor Determinan PDB Negara Anggota G20 - Pascal, Emilio; Muchtar, Masruri; Sihombing, Pardomuan Robinson (Sosio e-Kons, 2023)
This study develops the Solow growth model to explore the determinants of GDP. The purpose of this study is to examine which factor has the most influence on GDP. This study uses panel data regression. The variables used include GDP, FDI, productivity, labor, and the inflation rate during the 2012-2017 period obtained from the World Development Indicators, World Bank. The results showed that the labor and productivity variables had a significant positive impact on GDP. Meanwhile, FDI has no significant adverse effect on GDP. Inflation has no significant positive impact on GDP. The government can focus on increasing labor productivity to reap significant returns on economic growth. The recommendation from this research is that the government should formulate policies that can boost productivity to boost economic growth by providing skills training programs for prospective workers, as well as providing incentives so that more jobs can absorb labor and create competition.